A Cross-Cultural Study of Criticism Strategies: Iraqi and Malay ESL Learners (Journal of the College of Basic Education, 2022)
Criticism, as an evaluative criterion, is a significant speech act for English language learners to improve their speech and actions in their academic life. Yet, it is realized differently across diverse cultures. Few studies have shown that the linguistics forms of one language are different from those available in another language. Hence, this study aims to investigate the cross-cultural similarities and differences between 60 Iraqi and Malay university learners in the use of criticism strategies. The data are collected using a Discourse Completion Test (DCT) and a Focus Group Interview (FGI). The data are coded based on Nguyen’s (2005) coding scheme of criticism in terms of the realization strategies. Qualitative and quantitative approaches are used in the analysis of data. The findings evidently uncover that both groups use similar categories of criticism strategies, but Iraqis use more direct criticisms than Malays who opt for indirectness in their criticisms. Finally, some pedagogical implications for teachers of English as a second or foreign language are provided in this study.